Pembuatan Video Penyuluhan Berita Palsu Terkait COVID-19 bagi Masyarakat Kota Batam - Satriya Bayu Aji; Condra Antoni; Yosi Handayani; Nur Rahmah Andayani; Slamet Soebagiyo; Arta Uly Siahaan; Tian Havwini; Jhon Hericson Purba; Abdurahman Musa (Pusat P2M Politeknik Negeri Batam, 2021)
The terror of the deadly COVID-19 pandemic that is happening right now becomes more and more intimidating with the rapid circulation of information in massive quantities about this outbreak. Of the various news coming out every day, some are valuable, others might be less useful. However, some of them may cause more harm than good. The problem is how to sort the incoming information and determine whether it is reliable. In this community service project, a public service announcement will be produced with the intention of informing the public about some rumors and misconceptions that have been spreading in society. It is hoped that the announcement will unravel the truth and clear any confusion that is happening. The content of the announcement is based on the Myth Busters page on the official WHO website. It will then be broadcasted by Batam TV. To find out how the viewers perceive the public service announcement, an online survey is conducted, which can be accessed by the viewers by scanning the QR code displayed at the end of the announcement. The results of the survey show that most viewers consider the announcement easy to understand, useful, up to date, and motivating, in addition to having a good mix of attractive colors and clear sound. However, public service announcements on local television channels are no longer the main source of information for citizens of Batam, especially in the context of COVID-19.